Subjective cognitive decline, APOE ε4, and incident mild cognitive impairment in men and women - Müller-Gerards, Diana (Alzheimers Dement (Amst), 2019)
INTRODUCTION: Possible joint effects of subjective cognitive decline (SCD) and apolipoprotein E (APOE) ε4 genotype on incident mild cognitive impairment (MCI) were examined for men and women separately. METHODS: Cognitively normal participants with and without SCD were included from the first follow-up examination of the population-based Heinz Nixdorf Recall study. Sex-stratified logistic regression models estimated main effects and interactions (additive, multiplicative) of SCD at the first follow-up (yes+/no−) and APOE ε4 (positive+/negative−) groups for MCI 5 years later. RESULTS: Odds for MCI 5 years later were higher in SCD/APOE ε4 group +/+ than the sum of groups +/− and −/+ in women, with a trend for positive interaction. Odds for incident MCI in men was highest in group +/−, with no interaction effect. DISCUSSION: Our findings indicate that APOE ε4 may play an important role in the association of SCD and incident MCI, especially considering sex. Further studies need to examine these associations with larger sample sizes.